Evaluación de dos metodologías de la extracción de la fibra del (Cannabis sativa L.) - Chacán Campos, Jazmín Stefanía (2022)
In Ecuador there are no indications that the extraction of the fibers from the stem of Cannabis sativa L has been carried out, much less for industrial purposes because the main problem that it presented to the industry was the penalization of the plant, which is why The Organic Law for the Comprehensive Prevention of the Socioeconomic Phenomenon of Drugs and for the Regulation and Control of the Use of Cataloged Substances Subject to Supervision was reformed, which entered into force on June 21, 2020, giving rise to the new cannabis industry, being an alternative that generates employment in some sectors of the country through the development of new lines of research since it has adequate characteristics for the creation of different products due to its hardness and resistance, currently in Ecuador there are 705 companies nationwide, of which Cannandes and EcuaCáñamo stand out. are dedicated to the cultivation of the plant, for this reason the present research project had as its objective e evaluation of two methodologies for extracting the fiber of Cannabis sativa L for industrial purposes in which the biological method was used with retting with stagnant water and the chemical method with hydrogen peroxide and sodium hypochlorite, also in this investigation. Descriptive statistics were applied to the variables under study, such as the weight of fine, short and tow fiber, as well as the percentage of moisture, density, crude fiber, cellulose, lignin, and yield. Next, a physicochemical analysis was carried out at the SeidLaboratory Laboratory and the Resistance of Materials and Geotechnical Laboratory of the Faculty of Engineering of the Pontifical Catholic University of Ecuador of the fiber obtained, in which the following results were obtained by the biological method: fiber with 11.21% moisture, 69.76% cellulose, 9.95% lignin, 0.0523 g/ml density, 68.15% crude fiber and a yield of 8.4% while by the chemical method obtained a fiber with 13.91% humidity, 64.31% cellulose, 8.18% lignin, 0.0372 g/ml density, 63.10% crude fiber and a yield of 9.8%. Finally, a cost determination was carried out for industrial purposes of cannabis fiber where a cost of $49.06 for the production of 100 g of fiber was calculated for the biological method, that is why for the sale of 1 g this would cost 0.49 cents while for the chemical method a cost of $75.54 for the production of 100g of fiber is why for the sale of 1g this would cost 0.75 cents being not viable in the production in the market it was also formulated a proposal as an alternative for the use of fiber in the production of kraft paper, biodegradable packaging and eco-bricks. Deducing that the best extraction method is the biological method because it presented better quality parameters and lower production cost.